2016
DOI: 10.1016/j.drugpo.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The users of Novel Psychoactive Substances: Online survey about their characteristics, attitudes and motivations

Abstract: Understanding the different motivations for NPS use in terms of drug groups could enable more effective prevention and consequently a reduction in harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 21 publications
5
108
0
Order By: Relevance
“…Concerns were evident within these communities with regard to unpleasant effects of synthetic cannabinoids and inconsistent content of MDMA, often containing other NPS such as MDPV, Methylone and 4-MMA. Similar trends are reported in GDS (2016) and by Soussan & Kjellgren, (2016).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Concerns were evident within these communities with regard to unpleasant effects of synthetic cannabinoids and inconsistent content of MDMA, often containing other NPS such as MDPV, Methylone and 4-MMA. Similar trends are reported in GDS (2016) and by Soussan & Kjellgren, (2016).…”
Section: Discussionsupporting
confidence: 75%
“…Online retail is reported to be one sourcing route for NPS, in addition to offline interactions via friends and local contacts (Sande, 2016;Soussan & Kjellgren, 2016;van Amsterdam et al, 2015). The Surface Web is used in the accessing of information around retail, synthesis and cultivation processes, and how to circumvent national legislative controls (Lavorgna, 2014(Lavorgna, :2016van Amsterdam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Motives for use are similiar to that reported elsewhere ( Van Hout, 2014;Van Hout & Hearne, 2015;Soussan & Kjellgren, 2016;GDS, 2016). Despite legislation viewed as cross cutting between law enforcement and health (Ryall and Butler, 2011); service responses and preventative measures have not kept up with the increase in poly drug referrals which involve NPS, and the diverse range of NPS used in Ireland.…”
Section: 'The Primary Target Audience For the Current National Drug Ssupporting
confidence: 60%
“…The users' emphasis on the pleasurable effects is important to acknowledge from a prevention perspective, especially since a previous study has revealed that the main incentive for use of Novel Psychoactive Substances (NPS) in general, and for novel opioids in particular, was "pleasure and enjoyment" [21]. The present study found frequently occurring descriptions of a pleasant, relaxed and tranquil state in which the persons felt very content with "just being".…”
Section: Discussionmentioning
confidence: 62%
“…It has earlier been elucidated that "habit and addiction" constituted a considerable incentive for use of novel opioids [21]. A few persons in the present study explicitly described themselves as opioid dependant, and they reported use of MT-45 or AH-9721 as a means to cope with withdrawal effects from other opioids like oxycodone or heroin.…”
Section: Discussionmentioning
confidence: 79%